Examining the Reaction Times of International Level Badminton Players Under 15 - Mehmet Fatih Yüksel; Gülsen Tosun Tunç (MDPI AG, 2018)
This research was conducted to examine the simple visual and auditory reaction times of badminton players of the national teams and to examine the possible effects of reaction-time average values of badminton players under the age of 15 who participated in the fifth International Rumi Child Sport Games. In total, 48 players (male = 24; female = 24) from six countries (Turkey, Azerbaijan, Bulgaria, Macedonia, Serbia, Georgia) participated in the study. Stature, bodyweight, BMI, dominant and non-dominant hand visual and auditory reaction time values of the participants were detected. At the end of the study, it was determined that there were statistically significant differences between the countries in terms of male dominant and non-dominant hand visual reaction values, and male dominant hand auditory reaction values. It was also determined that there were statistically significant differences between the countries in terms of female bodyweight, BMI, dominant and non-dominant hand visual reaction values, and female non-dominant hand auditory reaction values. There was statistically significant difference between female and male players with regards to dominant and non-dominant hand visual, and non-dominant hand auditory reaction values. In conclusion, it was determined that the reaction times of the top ranking countries in the fifth International Rumi Child Sport Games under-15 were at a better level, and it can be concluded that this factor played an important role for success alongside with technique and tactic features.